2021
DOI: 10.1097/tp.0000000000003570
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Glomerular Size With Donor–Recipient Factors and With Response to Injury

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…A recent study on the basis of biopsies for cause suggested that smaller glomeruli late after transplantation (a mean of 7.7 years after-transplant) were associated with worse graft survival. 9 We confirmed this in our study of purely surveillance (not for cause) biopsies, although with an adjustment for all The cv score could not be graded in nine 5-year biopsies. Banff scores, the association between smaller glomeruli at 5 years and poor graft survival was attenuated.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…A recent study on the basis of biopsies for cause suggested that smaller glomeruli late after transplantation (a mean of 7.7 years after-transplant) were associated with worse graft survival. 9 We confirmed this in our study of purely surveillance (not for cause) biopsies, although with an adjustment for all The cv score could not be graded in nine 5-year biopsies. Banff scores, the association between smaller glomeruli at 5 years and poor graft survival was attenuated.…”
Section: Discussionmentioning
confidence: 93%
“…In both studies, biopsies with larger glomeruli had lower Banff scores, with the exception of those with cg scores-a rare histologic finding in both studies. 9 To our knowledge, our study is the first to assess the late percentage of ischemic glomeruli and the late percentage of GSG in transplant surveillance biopsies. One novel finding in this study was that compared with implantation biopsy, glomerulosclerosis was similar at the 1-year biopsy, whereas the percentage of ischemic glomeruli was almost five-fold higher.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Measuring glomeruli would seem like a good idea, and multiple studies in transplanted and native kidneys have found relationships with glomerular size with outcomes, although not always in a common direction. 1,2 In current study published in this edition of Transplantation , 3 Grande et al obtained 1027 indication biopsy samples for transplant dysfunction and measured glomerular planar surface area and diameter by image analysis on all glomeruli containing a vascular pole (excluding sclerosed glomeruli) from the 2 cohorts of the Deterioration of Kidney Allograft Function study. BKV infection and recurrent glomerulonephritis were excluded.…”
Section: Commentarymentioning
confidence: 99%